Meningkatkan Hasil Belajar Pakat Dan Mandiri Melalui Model Discovery Learning Fase A SDN 173524 Balige - Lusiana Sihaloho (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Abstract. The purpose of this Classroom Action Research is to determine and measure the increase or not of the improvement or not of grade II students of SDN 173524 Balige, Balige District, Toba Regency, North Sumatra Province with the Discovery Learning Method. The subjects of the study were 6 grade II students of SDN 173524 Balige, consisting of 4 men and 2 women. The object of research is the results of learning and independent students in the study of Catholic Religion and Ethics in the material of teaching module 1 "Jesus Offered in the Temple" and increasing in teaching module 2 "Jesus Found in the Temple". With data collection techniques are observation, documentation and tests. The results showed that there was an increase in learning outcomes and independence of Class II students on the material "Jesus Offered in the Temple" by applying the Discovery Learning method in cycle II of the material "Jesus Found in the Temple". The increase in learning and independent outcomes is evidenced by the average score of independent improvement in cycle I is 60.5% and in cycle II it increases by 25% which is 85.5%. And the increase in learning outcomes in cycle 1 was 67% and in cycle II it increased by 27% which is 94%.